Special Economic Zones Law and Policy Perspectives - Basedow, Jürgen; Su, Chen (Mohr Siebeck, 2023)
By their very nature, Special Economic Zones encompass various elements studied in the academic disciplines of economics, political science and law. While their objectives are determined by economics, and their structures, implications and limits by law, their implementation requires a certain combination and cooperation of political forces, something which has been the subject of political science enquiries. A conference held at Kyushu University in Fukuoka convened scholars from all these disciplines to put Special Economic Zones into perspective. The papers presented highlighted functions and structures, historical aspects, the political dimension and foreign equivalents of deregulation, the interplay of such zones, and constitutional considerations. Freedom of contract and competition law, plus the effects that these economy-boosting tools may have on labour and innovation are also dealt with.